Error Analysis of Composition Writing: A case of Saudis EFL University Students - Salih, Abdulgalil Abd Allah (IJRDO- Journal of Educational Research, 2018)
The study aimed at identifying and classifying the errors that committed by Saudi students of English in composition writing based on analytical, descriptive method. The study has reached to many findings of it: Syntactic, Lexical and mechanism errors with different degrees of occurrence. As subcategory of syntactic category, verb agreement errors were the most frequently occurring with 42%. Whereas wrong word choice comes as highest lexical errors committed by the respondent with 72%. Spelling errors, which was subcategory of mechanism were at the top of errors that committed by the very same respondents with 75%. MT interference may be one of the main sources in committing these errors. The subjects directly translate the Arabic words into English equivalents which led to incorrect of sentences. The study recommended the necessity of given more care to composition writing, as well reading, this will help students developing their English language, as will lead them to avoid committing Syntactic, Lexical and mechanism errors. For this researchers ought to carry out depth studies to address the area of composition writing.